STRUCTURE FOR REDUCING THERMAL DISPLACEMENT OF MACHINE TOOL STRUCTURE - GIM, TAE WEON; LEE, SANG KYOO; KIM, WON NYUN; LEE, YOON JONG (2013)
The present invention pertains to a structure for reducing the thermal displacement of a machine tool structure. The structure for reducing the thermal displacement of a machine tool structure, according to the present invention, includes: a fixed structure (100) which is provided to a machine tool and has a guide rail (102) formed at one side; a movable structure (120) which is mounted to the guide rail (102) and carries out movement; and a cooling section (300) which circulates cooling oil in the fixed structure (100) for cooling the fixed structure (100) and makes the temperature distribution of the fixed structure (100) uniform. The cooling section (300) includes a first cooling unit which is disposed in the fixed structure (100) so as to be adjacent to the guide rail (102) and carries out heat exchange between heat generated in the guide rail (102) and the cooling oil; a second cooling unit which is disposed at the side lower than the first cooling unit at an interval with reference to the entire construction of the fixed structure (100) for carrying out heat exchange; and a pump section (400) which is disposed at one side of the cooling section (300) and forces the cooling oil to circulate along the first and second cooling units. La présente invention concerne une structure permettant de réduire le déplacement thermique de la structure d'une machine-outil. La structure permettant de réduire le déplacement thermique de la structure d'une machine-outil selon l'invention comprend : une structure fixe (100) qui est montée sur une machine-outil et présente un rail de guidage (102) formé d'un côté : une structure mobile (120) qui est montée sur le rail de guidage (102) et effectue un mouvement ; et une section refroidissement (300) qui fait circuler de l'huile de refroidissement dans la structure fixe (100) pour le refroidissement de la structure fixe (100) et confère à la structure fixe (100) une distribution uniforme de la température. La section refroidissement (300) comprend : une première unité de refroidissement qui est disposée dans la structure fixe (100) de manière à être adjacente au rail de guidage (102) et qui effectue un échange de chaleur entre la chaleur générée dans le rail de guidage (102) et l'huile de refroidissement ; une seconde unité de refroidissement qui est disposée sur le côté plus bas que ne l'est la première unité de refroidissement à une certaine distance par rapport à l'ensemble de la structure fixe (100) pour effectuer l'échange de chaleur ; et une section de pompage (400) qui est disposée sur un côté de la section de refroidissement (300) et force l'huile de refroidissement à circuler le long de la première et de la seconde unité.